Analisis Kemacetan Kota Makassar Dengan Menata Ruang Parkir Jalan - Suriadi, Suriadi; Nurdin, H. Abd. Rahim; Yunus, Ahmad Yauri (Program Studi Teknik Sipil Universitas Bosowa, 2026)
This research ,highlight traffic jam problem that in the city of Makassar , especially pengayoman road Panakkukang .the traffic that because parking activity in the road which reduce effective traffic lanes, disrupting the smooth flow of traffic with rapid economic growth in Makassar increase traffic movement is unavoidable which further worsen traffic jam condition the aim of this research is to analyze the impact of in the street parking on traffic performance to provide parking control solution in the area they used metode involves direct observation of three different points on the pengayoman road section with data collected including traffic volume ,parking and performance of the road section ,observation were Carrie out on Wednesday ,Saturday and Sunday to get more comprehensive picture the result of the research showed that the highest volume of traffic flow on the pengayoman road section reached 6864 the Passengers car unit per hour (per hour) with degree of saturation (DS) of 0,77 the service level indeks shows category D ,which indicate an unstable level of service and category A for the highest level of service and these result can be concluded that parking activities on the road significantly reduce road capacity which has a negative impact on performance at the location.